Cellular Mechanisms of Cortisol-Induced Changes in Mauthner-Cell Excitability in the Startle Circuit of Goldfish - Bronson, Daniel R.; Preuss, Thomas (Frontiers in Neural Circuits, 2017)
Predator pressure and olfactory cues (alarm substance) have been shown to modulate Mauthner cell (M-cell) initiated startle escape responses (C-starts) in teleost fish. The regulation of such adaptive responses to potential threats is thought to involve the release of steroid hormones such as cortisol. However, the mechanism by which cortisol may regulate M-cell excitability is not known. Here, we used intrasomatic, in vivo recordings to elucidate the acute effects of cortisol on M-cell membrane properties and sound evoked post-synaptic potentials (PSPs). Cortisol tonically decreased threshold current in the M-cell within 10 minutes before trending towards baseline excitability over an hour later, which may indicate the involvement of non-genomic mechanisms. Consistently, current ramp injection experiments showed that cortisol increased M-cell input resistance in the depolarizing membrane, i.e., by a voltage-dependent postsynaptic mechanism. Cortisol also increases the magnitude of sound-evoked M-cell PSPs by reducing the efficacy of local feedforward inhibition. Interestingly, another pre-synaptic inhibitory network mediating prepulse inhibition (PPI) remained unaffected. Together, our results suggest that cortisol rapidly increases M-cell excitability via a post-synaptic effector mechanism, likely a chloride conductance, which, in combination with its dampening effect on feedforward inhibition, will modulate information processing to reach threshold. Given the central role of the M-cell in initiating startle, these results are consistent with a role of cortisol in mediating the expression of a vital behavior.